Analysis of Learning Speaking Skills Using the WhatsApp Application in Elementary Schools. Issue 1 (March 2021) - Fahrudin, Sigit Hasan; Winarni, Retno; Winarno,
Abstract: The Covid-19 pandemic approaching the 21st century has had a significant impact in all fields, including education. Finally, all learning activities are carried out online or online. This study aims to analyze the implementation process of learning speaking skills using the WhatsApp group application, the obstacles faced, and the teacher's efforts to improve speaking skills. This research was conducted at SD Negeri Katikan 1 and SD Negeri Katikan 2, Kedunggalar District, Ngawi Regency, East Java. This research uses descriptive qualitative research methods. The subjects used in this study were teachers of class V SD Negeri Katikan 1 and SD Negeri Katikan 2. The sampling technique used was purposive sampling. Data collection techniques used in this study were in-depth interviews and document analysis. Data analysis used interactive analysis techniques by Miles and Huberman. The result of this research is that the Covid-19 pandemic has had a huge impact on the learning process, learning elementary school speaking skills which are usually carried out offline has now been converted into online or online learning via WhatsApp. Learning of speaking skills is carried out through the WhatsApp feature, video calls, learning videos, pictures, and voice notes. Barriers to online learning are network problems, ownership of an android cellphone, and student discipline. The efforts made by the teacher to improve students' speaking skills in online learning through WhatsApp is to familiarize students with speaking in every learning activity, such as apperception activities, core activities (presentation of material and assignments), and other activities (leading prayer, presentation).